Genetic variations for post emergence herbicide tolerance in field pea (Pisum sativum) - PARIHAR, A K; KUMAR, N; NATH, C P; SINGH, A K; CHATURVEDI, S K; DIXIT, G P; SINGH, N P (The Indian Journal of Agricultural Sciences, 2019)
Weeds are highly competitive to the crops for nutrient and water from soil, sunlight, space and also harbour many insect-pest and diseases, consequently lead to drastic yield reduction. Pisum sativum is sensitive to the most of the potential post emergence herbicides and thus, effective weed management is a difficult assignment particularly the later flush of weed emergence. The identification of herbicide resistant genotypes is the potential way to develop herbicide tolerant varieties as well as to control weeds and minimise yield losses. So far no report is available for herbicide tolerant genotypes in field pea. Therefore, an attempt has been made to identify the genotypes as a source of resistance to the post-emergence herbicide metribuzin. Total 822 genotypes were examined for their sensitivity under preliminary screening against metribuzin at 0.5 kg ai/ha during the winter season of 2015-16. Of the tested genotypes, a set of 85 promising genotypes were re-evaluated with same dose during the winter season of 2016-17 with visual phyto-toxicity score. The results of experiment revealed that there was a huge amount of genetic variation for tolerance against metribuzin in field pea. The frequency distribution grouped the genotypes as tolerant (1), moderately tolerant (5), susceptible (18), and highly susceptible (61) categories. None of the genotypes showed highly tolerant reaction. Notably, accession P-637 witnessed tolerance and other five accessions, viz. P-729, P-647, P-1075, P-2016, and P-1448-2 registered moderately tolerance reaction against metribuzin. Hence, aforesaid promising genotypes may be utilized as donor to speed up breeding for development of herbicide tolerant varieties in field pea and in other genetical studies too.